Pengembangan Media Magic Disc Untuk Pembelajaran Al-Qur'an Hadist Materi Tajwid di MTS NU Al-Badar Kaliwining Rambipuji - Mukaromah, Siti Luluk (Pendidikan Islam Pascasarjana IAIN Jember, 2024)
Tajweed material is a science that studies the rules for reading the Qur'an and the laws of each reading. Mastery of tajweed material in reading the Qur'an is one of the goals in learning Al-Qur'an Hadith. However, students still often have difficulty in distinguishing the type of law of each reading. This is a challenge for Al-Qur'an Hadith teachers in teaching tajweed material to students. Therefore, this development research develops magic disc media for tajweed science. The formulation of the problems of this research and development are: 1) How is the development of magic disc media 2) How is the validity of magic disc media 3) How is the effectiveness of magic disc media for learning Al-Qur'an Hadith tajweed material at MTs NU Al Badar Kaliwining Rambipuji? The objectives of this research and development are: 1) developing magic disc media 2) testing the validity level of magic disc media 3) testing the effectiveness of magic disc media for learning Al-Qur'an Hadith at MTs NU Al Badar Kaliwining Rambipuji. This research is classified as development research using the borg and gall development model design. The research instrument consists of material and media expert validation questionnaire instruments, student and teacher response questionnaire instruments. The validation analysis is based on the validation expert's assessment and the effectiveness analysis uses a one group pretest posttest type quasi-experiment analysis with the calculation of N-Gain and T test. The results of development research related to validity obtained a percentage of 90% from material experts in the “very valid” category, 79% from media experts in the “valid” category, 100% from teacher responses in the “very valid” category, and 94.3% from student responses in the “very valid” category. For effectiveness through pretest and posttest, the average pretest result was 46.5 and posttest was 92.75. Based on the n-gain test using Ms. Excel calculations obtained an average of 0.833726 where 0.833726> 0.7 while the t test using SPSS calculations obtained a t-count of 7.663 with a t-table of 2.100 so it can be said that the t-count> ¬t-table is 7.663> 2.100 with a significance result of 0.000 which is 0.000 <0.05, it can be concluded that the magic disc learning media for tajwid science at MTs NU Al Badar Kaliwing Rambipuji is said to be “effective”.